Analysis of the Chemistry of Ni-Base Turbine Disk Superalloys Using An Alloys-By-Design Modeling Approach - Crudden, D; Raeisinia, B; Warnken, N; Reed, R (2013)
The chemistry of the Ni-base superalloys used for turbine disks is critiqued by making use of the recently developed Alloys-By-Design computer-based tools. Compositions within the Ni-Cr-Co-Al-Ti-Mo-W-Ta(-Zr-C-B) design space are evaluated virtually. The assessment is made on the basis of sub-models for yield strength, creep behavior, oxidation resistance, and density; microstructural factors such as γ′ volume fraction and γ′ solvus temperature are considered where needed. The trade-offs between the different factors are studied in a quantitative sense. Diagrams are developed for the different alloy properties to highlight the limitations and challenges that one encounters when designing new grades of alloy or when optimizing existing grades. Composition-property maps are constructed that allow for an informed approach when defining an alloy composition. Specifically, the impact of chromium, molybdenum, and tungsten additions when mechanical behavior and lifing considerations are of concern is demonstrated. © 2012 The Minerals, Metals and Materials Society and ASM International.